Discriminant Effect of NEAZDP on the Livelihoods of Beneficiary Communities in Yobe State of Nigeria - Sadiq, Sanusi Mohammed; Grema, Isiyaku Jawa (Jordan Journal of Agricultural Sciences, 2025)
The discriminant effect of NEAZDP on the livelihoods of beneficiary communities in Yobe State, Nigeria, highlights the need to address disparities in socio-economic outcomes and structural barriers limiting the program’s equitable and sustained impact. Consequently, this study examines the structural (programme) and endowment effects on the livelihood status of beneficiaries, comparing results across beneficiary, spill-over, and control groups. Further, using a multi-stage sampling technique, the study used a cross-sectional survey data elicited through a well-structured questionnaire coupled with an interview schedule from a total of 396 respondents spread across the treated and untreated communities of Nigeria’s Yobe State. Moreover, strictly using inferential statistics, the goals of the study were achieved. In the short term, statistical analysis demonstrates significant improvements in the livelihoods of NEAZDP participants, with results indicating that the programme addresses specific needs and enhances economic outcomes for beneficiaries. However, long-term analysis reveals a decrease in livelihood status among beneficiaries relative to spill-over groups, suggesting potential challenges in sustaining the programme’s positive effects. Through Oaxaca-Blinder decomposition, the study finds that while beneficiaries have favorable socio-economic characteristics, structural barriers within the programme limit their livelihood gains. Spill-over groups, despite non-participation, experience indirect benefits, hinting at broader community impacts. Recommendations include enhancing structural support, refining program interventions, and leveraging spill-over effects to maximize the programme’s reach. This analysis underscores the need for continuous monitoring and adaptation to maintain NEAZDP's effectiveness in fostering sustained livelihood improvements among beneficiaries.